Screening and Identification of Mangrove Plant Sonneratia alba Sm. Endophytic Bacteria From Enggano Island, Bengkulu Province - Fatimatuzzahra, Fatimatuzzahra; Wibowo, Risky Hadi; Sipriyadi, Sipriyadi; Simanjuntak, Putri Hezekiel Claracia; Johan, Yar (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Abstract: The mangrove plants from Enggano Island are found in a well-preserved ecosystem. Mangroves contain secondary metabolite compounds that result from the interaction between plants and endophytic bacteria. This study aims to obtain endophytic bacterial isolates from the mangrove plant Sonneratia alba Sm. from Enggano Island and to assess bacterial diversity. Endophytic bacteria were isolated using grinding and then diluted with serial dilutions of 10-1, 10-3, and 10-5. The growing bacteria were purified using the quadrant streak method. They were then identified by observing colony morphology, Gram staining, and biochemical tests including catalase, motility, citrate, urea, and sugar fermentation tests. Bacterial identification was carried out using Bergey's Manual of Determinative Bacteriology. A total of 22 endophytic bacterial isolates were collected from the mangrove plant Sonneratia alba from Enggano Island, consisting of 4 genera: Bacillus, Marinococcus, Micrococcus, and Pseudomonas. There were 17 isolates closely related to the genus of Bacillus, 1 isolate closely related to the Marinococcus, 2 isolates closely related to the Micrococcus, and 2 isolates closely related to the Pseudomonas.Abstrak: Tumbuhan mangrove asal Pulau Enggano berada pada ekosistem yang masih terjaga. Mangrove memiliki kandungan senyawa metabolit sekunder yang merupakan hasil interaksi antara tumbuhan dan bakteri endofit. Penelitian ini bertujuan untuk memperoleh isolat bakteri endofit tumbuhan mangrove Sonneratia alba Sm. asal Pulau Enggano dan mendapatkan keanekaragaman bakteri. Isolasi bakteri endofit dilakukan dengan metode gerus, kemudian diencerkan dengan pengenceran berseri dari 10-1, 10-3, dan 10-5. Bakteri yang tumbuh dimurnikan dengan metode gores kuadran. Kemudian diidentifikasi dengan mengamati morfologi koloni, pewarnaan Gram, dan uji biokimia meliputi uji katalase, uji motilitas, uji sitrat, uji urea, uji gula-gula. Kemudian dilakukan identifikasi bakteri dengan buku Bergey’s Manual of Determinative Bacteriology. Total isolat bakteri endofit yang berhasil dikoleksi dari tumbuhan mangrove Sonneratia alba asal Pulau Enggano adalah sebanyak 22 isolat dengan keanekaragaman bakteri endofit yang terdiri dari 4 genus yaitu Bacillus, Marinococcus, Micrococcus, dan Pseudomonas. Isolat yang memiliki kedekatan dengan genus Bacilus adalah sebanyak 17, yang memiliki kedekatan genus Marinococcus hanya 1 isolat, yang memiliki kedekatan dengan genus Micrococcus adalah 2 isolat, dan 2 isolat memiliki kedekatan dengan genus Pseudomonas.